Antitumor Enzyme L-Lyzine-α-Oxidase from Trichoderma harzianum Rifai F-180 and Investigation of Its Action on L-Lysine Oxidation by Capillar Electrophoresis - I. P. Smirnova; V. M. Shkinev; A. V. Rudnev; O. M. Kuznetsova; E. V. Karimova; V. S. Orlova (Антибиотики и Химиотерапия, 2020)
Trichoderma harzianum Rifai F-180, an organism producing the antitumor enzyme L-lysine-α-oxidase was cultivated and the enzyme was isolated and purified under the manufacturing conditions. The effect of L-lysine-α-oxidase on oxidation of L-lysine was investigated for the first time by capillary electrophoresis and the procedure conditions were developed. The reaction of L-lysine oxidative deamination is described and location of the reaction components picks on the elecrophoregrams was identified. The average rate of the catalytic reaction of L-lysine oxidation equal to 0.46 RU/min (7.7х10-3 RU/sec) was determined. The use of the antitumor enzyme L-lysine-α-oxidase is recommended as a drug for the treatment of superficial tumors and tissue relative oxygen excess.